USING CUE CARDS TO IMPROVE STUDENTS’ WRITING SKILLS - Hanafi Wibowo; Dyah Eka Putri (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2022)
Abstract: The objectives of the research are to identify whether cue cards could improve students’ writing skills. This research was carried out at SMK HUTAMA Bekasi. It was conducted from July 2021 to March 2022. The subject of the research was the students of class X TKJ class. The research method was Classroom Action Research and it was conducted in two cycles. In collecting the data, the researcher used interviews, observation, diaries, document, and test. Having collected the data, the researcher analyzed them both qualitative and quantitative data. The qualitative data were analyzed using interactive model; they are data reduction, data display, and data verification. The qualitative data were analyzed by using descriptive statistics to calculate the mean scores of the pre-test, post-test 1, and post-test 2. The results of this study indicate that the cue card technique can improve students' writing skills in descriptive texts. From the aftereffects of the discussion, the researcher reasoned that in this review there was an increment in understudies' composing abilities in descriptive texts. The average pre-test and post-test scores in cycles 1 and 2 are more revealing. The average score before the students learnt by cue cards was 62, according to the pre-test computation. After treatment, the average score increased to 74 (cycle 1), while the average score of post test 2 was 82 (cycle 2).